Proposta de um novo modelo de governan??a no setor de quimioterapia - Messias, Luis Renato Rotta (2016)
Chemotherapy is still a main way to fight cancer and consequently, the demand for its treatment accompanies increased incidence and prevalence of disease. Provided most recommended type of therapy, chemotherapy is responsible for greatest impact on treatment cost. In this sense, this research proposes a method that helps management of chemotherapy schedule, improving issues related to logistics characteristics and time constraints so that treatment becomes more effective. From January 2012 to December 2013, data were collected relating production, costs of major inputs, loss of prepared medicines and chemotherapies relationship conducted with inpatients and outpatients, all related to proposed change in the management model of Oncology sector from a public hospital located at S??o Paulo state. As usual flow consisted of patient medical examination, with treatment prescribed by doctor, the new proposed protocol determined that the schedule no longer take place by the medical action, but by pharmacist, in the sense that he is professional manager, capable to accurately assess variables such as time, cost, competition for resources and optimization of infusion bags. As a result, the study showed increased number of outpatients and decrease number of inpatients, which generates cost savings. There was fourfold increase in total number of patients seen per year, with financial resources invested remaining stable. This study showed that new approaches to follow the flow model proposed here, would optimize resources, serving a larger number of patients, maintaining quality of processes, confidentiality of information, and saving costs and inputs. Furthermore, it was shown to be more effective multi scheduling, in which the physician says the protocol that will be used, the time will be used, and whether the patient is able to use, but with regard to the management of competing facilities as beds, interaction, armchair, chemotherapy or surgical room, a professional liability being with a logistics vision of the whole, in which case, a nurse or pharmacist